On calculation methods for the model of plates bending - Yessenbayeva, G.A.; Yesbayeva, D.N.; Makazhanova, T.Kh. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
The article is devoted to the study of plate bending problems, which are of great applied importance and are found everywhere in various branches of science and technology. In this article the structure of the calculation methods is described, their main components are highlighted; the classical approach of calculating rectangular plates hinged supported on two parallel sides and with arbitrary boundary conditions on each of the other two sides is characterized. The mathematical apparatus of the method of trigonometric series is presented in the volume necessary for calculating the plates. Special cases of the calculation for the bending of a rectangular plate by the Levi method are given. This article is focused mainly on mechanics, physicists, engineers and technical specialists.
Keywords: bending of a rectangular plate; plate deflection function; boundary conditions of the plate; equation of S. Germain; Navier solution; Levy solution